IKHWAN MODUS: DAMPAK DIGITALISASI NIKAH SYAR’I - Risris Hari Nugraha; Mita Mawadda; Sasetya Mustika Putri Candrama; Ernawati Ernawati; Muhammad Faozy Fathurohim (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Ta'aruf is an Islamic law that aims to identify potential partners before entering the marriage stage. In this case, ta'aruf is understood as the best way and is very different from courtship because it is able to avoid adultery, the risk of dangerous venereal diseases, and the risk of dangerous actions or other crimes. However, the fact is that ta'aruf also carries a risk of crime, and this only applies to online ta'aruf. The purpose of this study is to find out the background of the perpetrators under the guise of conducting online ta'aruf and the factors that cause fraud in online ta'aruf. In this study, the researchers used a mixed method or a combination of two methods, namely qualitative data in the form of descriptions or exposures and quantitative data in the form of numbers based on surveys. This research method uses a concurrent embedded design, which is a mixed research model that applies one-stage qualitative and quantitative data collection at a time. And researchers used qualitative data as primary data and quantitative data as secondary data. The results of this study indicate that the personality of the perpetrator is the main factor in the occurrence of social deviations in online ta'aruf. The lack of protection against the system and rules for online ta'aruf and the standard of public understanding of online ta'aruf and its deviations (Ikhwan Modus) are supporting factors for the occurrence of cybercrime cases.